Hedges and Boosters used by Becky Kennedy in the TED Talk - Rahmawati, Nofvy; Duwila, Shanty A.Y. P. S. (Indo-MathEdu Intellectuals Journal, 2024)
This research analyzes Becky Kennedy's use of hedges and boosters in the TED Talk "The Single Most Important Parenting Strategy." The aim is to describe the types of hedges and boosters used by Kennedy and determine the most frequently occurring categories. A qualitative descriptive method was used with data collection through visual perception of the talk show. The steps of data collection included: 1) searching for and downloading the TED Talk and its transcript, 2) watching the talk show repeatedly, 3) converting the Word document into Txt format, and 3) importing the transcript into AntConc.exe. The analysis technique used was content analysis using the following steps: 1) examining the text containing the words hedges and boosters, 2) classifying the types of hedges and boosters, 3) presenting the data in tables, 4) analyzing using Hyland's (1998) theory, 5) drawing conclusions. The results showed that Kennedy tended to use words in the modal verb category in hedges and boosters and indicated the dominance of Kennedy's use of modal verbs in strengthening or doubting his arguments in the speech.